The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s10648-020-09558-6
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent Do Situation-Model-Approach Interventions Improve Relative Metacomprehension Accuracy? Meta-Analytic Insights

Abstract: This meta-analysis investigated the extent to which relative metacomprehension accuracy can be increased by interventions that aim to support learners’ use of situation-model cues as a basis for judging their text comprehension. These interventions were delayed-summary writing, delayed-keywords listing, delayed-diagram completion, self-explaining, concept mapping, rereading, and setting a comprehension-test expectancy. First, the general effectiveness of situation-model-approach interventions was examined. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 77 publications
2
28
0
1
Order By: Relevance
“…Interestingly, all students overestimated their current understanding. This, however, is in line with prior research that highlighted that students generally tend to overestimate their current comprehension [85][86][87]. Nevertheless, we need to reject our hypotheses regarding effects on students' comprehension and their monitoring accuracy.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, all students overestimated their current understanding. This, however, is in line with prior research that highlighted that students generally tend to overestimate their current comprehension [85][86][87]. Nevertheless, we need to reject our hypotheses regarding effects on students' comprehension and their monitoring accuracy.…”
Section: Discussionsupporting
confidence: 86%
“…Generative Aktivitäten können auch dazu beitragen, den Lernerfolg indirekt zu unterstützen, indem sie Schülerinnen und Schülern dabei helfen, ihr eigenes Verstehen im Lernprozess genauer einzuschätzen. Ergebnisse aus der Metaanalyse von Prinz et al (2020) zeigen, dass Lernende durch die Vervollständigung von Diagrammen akkurater beurteilten, wie gut sie die Inhalte von Texten verstehen. Besonders wenn das Lernen unter Pandemiebedingungen allein stattfindet, ist eine genaue Überwachung der eigenen Verstehensprozesse wichtig, um das Lernen optimal zu steuern (Fischer et al 2020).…”
Section: Wie Kann Die Weiterverarbeitung Von Lerninhalten Gezielt Gefunclassified
“…Hence, the generative task of completing a think sheet might provide additional benefits for comprehension and transfer. Moreover, prior research has shown that generative tasks, such as constructing concept maps and completing diagrams, increase learners' metacomprehension accuracy because they provide learners with valid cues about their deeper understanding (i.e., their situation model; see, e.g., Griffin et al 2019;Prinz et al 2020;Van de Pol et al 2020). However, the generative tasks used in the prior research were not particularly designed to address misconceptions.…”
Section: Think Sheets As a Methods To Counteract Detrimental Effects Of Misconceptionsmentioning
confidence: 99%